Prediction of slurry operating temperature and biogas production rate using ambient temperature forecast as input parameter for underground brick-built biogas digesters. Issue 1 (31st December 2022) - Nekhubvi, V; Tinarwo, D
Abstract: The operational temperature of the biogas digester is the most critical parameter for optimum biogas production. Most household digesters are operated at ambient temperatures throughout the year. Biogas production rate increases with the increase of digester operational temperature. The present work focuses on developing a mathematical model to predict operating temperature from ambient temperature for underground built fixed dome Deenbandhu model digester. The operating or slurry temperature would then estimate the daily biogas production. Three fixed-dome underground brick-built biogas digesters of bulk size 6.0 m 3 constructed following a fixed-dome Deenbandhu model in India were used to study the operational temperature. Thermocouples were fitted in each digester to measure operational temperature data. The statistical tool R-studio was then used to establish the relationship between the operational and air temperature based on this arrangement. The results of this work provide information on the prevailing operating temperature for underground biogas digester systems and hence biogas production rate. The results from the study have shown that there is a strong correlation between bio-slurry temperature and ambient air temperature. Second, the biogas production was computed based on the data of the predicted slurry temperature. It was found that as the temperature increases, the production rate also increases.